PRE-DESIGN OF TILAPIA (OREOCHROMIS NILOTICUS) AND GENJER (LIMNOCHARIS FLAVA) PRODUCTION SYSTEMS IN THE BUCKET WITH ZERO WATER DISCHARGE (ZWD) SYSTEM. - Fawwaz Azmi, Muhammad
Determination of the right density of tilapia in a culture system in a bucket until it reaches the maximum carrying capacity is needed because it will affect the growth of fish. This study aims to determine the effect of different tilapia densities in bucket culture on absolute weight growth, absolute length growth, specific growth rate, survival rate, feed conversion ratio and determine the Von Bertalanffy equation for the growth of tilapia in a bucket culture system with genjer. The research was conducted at the Kost Sekar Tanjung, Caringin, Kab. Jatinangor, West Java from January to February 2021. The research design used RAK 2 groups (shaded and not shaded) with 4 treatments and 8 repetitions of density 3 fish/bucket (A), density 5 fish/bucket (B), density 7 fish/bucket (C), and a density of 9 fish/bucket (D). The results of the study analyzed by two-way ANOVA test at a 5% significance level with further tests the Duncan Multiple Range Test (DMRT) and Friedman's non-parametric statistical test at a 5% significance level. The calculation of the Von Bertalanffy equation model used the ELEFAN I method from FISAT II program. The results showed that the density treatment of tilapia gave a significantly different effect on absolute length growth and feed conversion ratio of tilapia in buckets with genjer plants. However, the treatment of tilapia density did not significantly affect the growth of absolute weight, survival rate, and specific growth rate of tilapia in a bucket with genjer. The analysis and data processing carried out resulted in the Von Bertalanffy equation for tilapia fish length with genjer plants is Lt=14,49(1- e(-0,82(t+1,45256))).